2019
DOI: 10.1186/s40545-019-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges constraining availability and affordability of insulin in Bengaluru region (Karnataka, India): evidence from a mixed-methods study

Abstract: Introduction Considering limited global access to affordable insulin, we evaluated insulin access in public and private health sectors in Bengaluru, India. Methods Employing modified WHO/HAI methodology, we used mixed-methods analysis to study insulin access and factors influencing insulin supply and demand in Bengaluru in December 2017. We assessed insulin availability, price and affordability in a representative sample of 5 public-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As noted earlier, GSDPs offered a better mix, that is, availability similar to that of private retail pharmacies but with better affordability (lower prices). Despite conspicuous affordability, popularity of Jan Aushadhi is low possibly because of poor governmental support, inadequate campaigning, inferior supply chain and negative perceptions about the quality of low-priced generics [41]. A systematic review reported that a significant proportion of both physicians and pharmacists consider generic medicines inferior, despite 35 of 38 trials demonstrating clinical equivalence between OB and generic versions of multiple CVD medicines [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, GSDPs offered a better mix, that is, availability similar to that of private retail pharmacies but with better affordability (lower prices). Despite conspicuous affordability, popularity of Jan Aushadhi is low possibly because of poor governmental support, inadequate campaigning, inferior supply chain and negative perceptions about the quality of low-priced generics [41]. A systematic review reported that a significant proportion of both physicians and pharmacists consider generic medicines inferior, despite 35 of 38 trials demonstrating clinical equivalence between OB and generic versions of multiple CVD medicines [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO included insulin analogues citing ‘lower incidence of symptomatic and nocturnal hypoglycaemia’ while acknowledging that the clinical benefits of analogues over human form are too small to justify the large price difference 11. This is more difficult to justify in countries with limited healthcare resources, especially India, where even human insulin continues to be unaffordable and poorly available despite being ‘essential’ since 1996 12…”
Section: Diabetesmentioning
confidence: 99%
“…One of the causes of low compliance to psychiatric medication is the high cost of the drugs, which many people from lower socioeconomic classes cannot afford, particularly when they are needed for an extended period. 4 Therefore, it is crucial to dispense high-quality medicines in sufficient quantities and at an affordable price to encourage treatment adherence. 5 A study on private pharmacies as healthcare providers in Odisha find that a large population prefer to use private pharmacies as compared to other public health providers, thus increasing their Out-of-Pocket (OOP) expenses.…”
Section: Introductionmentioning
confidence: 99%